2014
DOI: 10.1371/journal.pone.0096446
|View full text |Cite
|
Sign up to set email alerts
|

Economic Effects of Introducing Alternative Salmonella Control Strategies in Sweden

Abstract: The objective of the study was to analyse the economic effects of introducing alternative Salmonella control strategies in Sweden. Current control strategies in Denmark and the Netherlands were used as benchmarks. The true number of human Salmonella cases was estimated by reconstructing the reporting pyramids for the various scenarios. Costs were calculated for expected changes in human morbidity (Salmonella and two of its sequelae), for differences in the control programmes and for changes in cattle morbidity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…The costs of controlling foodborne diseases in food-producing animals are high and some studies have investigated the effect that a relaxation of the Swedish Salmonella control programme in food-producing animals would have on public health and societal costs [ 34 , 35 ]. They concluded that the number of reported domestic salmonellosis cases would increase substantially and the net cost effects would therefore be negative.…”
Section: Impact Measurements Of Foodborne Diseasementioning
confidence: 99%
“…The costs of controlling foodborne diseases in food-producing animals are high and some studies have investigated the effect that a relaxation of the Swedish Salmonella control programme in food-producing animals would have on public health and societal costs [ 34 , 35 ]. They concluded that the number of reported domestic salmonellosis cases would increase substantially and the net cost effects would therefore be negative.…”
Section: Impact Measurements Of Foodborne Diseasementioning
confidence: 99%
“…The costs related to VSCs and VSLs may potentially constitute a major part of the total costs [ 70 ] and excluding them probably leads to a considerable UE of the total societal costs. One study, in which the remaining life expectancy of persons who die as a result of salmonella infection was considered, found that including VSLs had only a minor impact on expected costs [ 4 ]. Although this study used VSL values that decrease proportionately with age, which is not supported by most studies [ 71 ], it nevertheless provides an indication of how much VSL costs would increase if age is considered for the main illnesses (for which the average age of cases that do not survive is rather high).…”
Section: Discussionmentioning
confidence: 99%
“…In Sweden, COI has previously been calculated for campylobacter and enterohemorrhagic Escherichia coli (EHEC), including a limited number of sequelae [ 3 ]. The method has also been used to test whether the Swedish salmonella control program should be modified based on a CBA [ 4 ]. On the other hand, the WTP approach includes intangible costs but only considers those parts of the direct and indirect costs that directly affect an individual.…”
Section: Introductionmentioning
confidence: 99%
“…One study, in which the remaining life expectancy of persons who die as a result of salmonella infection was considered, found that including VSLs had only a minor impact on expected costs [4]. Although this study used VSL values that decrease proportionately with age, which is not supported by most studies [71], it nevertheless provides an indication of how much VSL costs would increase if age is considered for the main illnesses (for which the average age of cases that do not survive is rather high).…”
Section: Discussionmentioning
confidence: 99%